Advancements in γδT cell engineering: paving the way for enhanced cancer immunotherapy - Yuan, Megan; Wang, Wenjun; Hawes, Isobel; Han, Junwen; Yao, Zhenyu; Bertaina, Alice (Frontiers in Immunology, 2024)
Comprising only 1-10% of the circulating T cell population, γδT cells play a pivotal role in cancer immunotherapy due to their unique amalgamation of innate and adaptive immune features. These cells can secrete cytokines, including interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α), and can directly eliminate tumor cells through mechanisms like Fas/FasL and antibody-dependent cellmediated cytotoxicity (ADCC). Unlike conventional αβT cells, γδT cells can target a wide variety of cancer cells independently of major histocompatibility complex (MHC) presentation and function as antigen-presenting cells (APCs). Their ability of recognizing antigens in a non-MHC restricted manner makes them an ideal candidate for allogeneic immunotherapy. Additionally, γδT cells exhibit specific tissue tropism, and rapid responsiveness upon reaching cellular targets, indicating a high level of cellular precision and adaptability. Despite these capabilities, the therapeutic potential of γδT cells has been hindered by some limitations, including their restricted abundance, unsatisfactory expansion, limited persistence, and complex biology and plasticity. To address these issues, gene-engineering strategies like the use of chimeric antigen receptor (CAR) T therapy, T cell receptor (TCR) gene transfer, and the combination with γδT cell engagers are being explored. This review will outline the progress in various engineering strategies, discuss their implications and challenges that lie ahead, and the future directions for engineered γδT cells in both monotherapy and combination immunotherapy.